Structural principles controlling HIV envelope glycosylation - Behrens, A; Crispin, M (Elsevier, 2017)
The heavily glycosylated, trimeric HIV-1 envelope (Env) protein is the sole viral protein exposed on the HIV-1 virion surface and is thus a main focus of antibody-mediated vaccine development. Dense glycosylation at the outer domain of Env constrains normal enzymatic processing, stalling the glycans at immature oligomannose-type structures. Furthermore, native trimerization imposes additional steric constraints, which generate an extensive ‘trimer-induced mannose patch’. Importantly, the immature glycans present a highly conserved feature of the virus that is targeted by broadly neutralizing antibodies. Quantitative mass spectrometry of glycopeptides together with structures of the trimeric viral-spike define the steric principles controlling processing and provide a detailed map of the glycan shield.